Together we deliver results achieved, lives improved. (Metro Manila, Philippines Asian Development Bank, 2018)
This publication showcases stories of successful partnerships between ADB and its member countries in Asia and the Pacific. This publication reflects on the enduring partnership of ADB with its developing member countries. These 10 stories illustrate how ADB, working with government and development partners, helps citizens respond to the varied needs of each country such as climate change mitigation, access to economic opportunities and social services, and disaster recovery. ADB approach to development continues to evolve with the needs of its regional members. Through innovation and strong partnerships, ADB remains committed to helping its members achieve the Sustainable Development Goals.
Keywords: Asian Development Bank; Public-private sector cooperation -- Asia; Public-private sector cooperation -- Pacific Area; Economic development; Electronic books